2016
DOI: 10.5551/jat.32904
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Epsilon 4 Enhances the Association between the rs2910164 Polymorphism of miR-146a and Risk of Atherosclerotic Cerebral Infarction

Abstract: Aim: To analyse the relationship between two potentially functional single-nucleotide polymorphisms (SNPs) of the miR-146a gene (rs2910164 and rs57095329) and the risk of atherosclerotic cerebral infarction (ACI).Methods: A total of 297 patients with ACI and 300 matched healthy individuals were enrolled in the study. The miR-146a polymorphism was detected using the polymerase chain reaction -restriction fragment length polymorphism method. Results: A significant difference in the C allele frequency at rs291016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Our meta-analysis, in contrast, suggests that this C allele is not significantly associated with IS risk; instead, we found the GG genotype of miR-146a (rs2910164) to be associated with increased risk. Our result may be more reliable than that of the previous meta-analysis by Zhu et al 39 because our meta-analysis contained nine more case–control studies 14 , 15 , 17 , 21 – 26 with larger samples. Our subgroup analysis suggesting a significant relationship between the C allele of miR-146a (rs2910164) and lower IS risk contained only one case–control study, which was by Jeon et al 16 …”
Section: Discussionsupporting
confidence: 59%
“…Our meta-analysis, in contrast, suggests that this C allele is not significantly associated with IS risk; instead, we found the GG genotype of miR-146a (rs2910164) to be associated with increased risk. Our result may be more reliable than that of the previous meta-analysis by Zhu et al 39 because our meta-analysis contained nine more case–control studies 14 , 15 , 17 , 21 – 26 with larger samples. Our subgroup analysis suggesting a significant relationship between the C allele of miR-146a (rs2910164) and lower IS risk contained only one case–control study, which was by Jeon et al 16 …”
Section: Discussionsupporting
confidence: 59%
“…Yet, the multiple roles of miRNAs in modulating ICAS progression may make it difficult to illuminate the exact mechanisms (Figure ). Besides, consideration of other factors that control miRNA regulation in ICAS, such as single nucleotide polymorphisms (Zhong et al, ) and lncRNAs (Huang, Wang, Mao, & Nan, ), may spread wider net of miRNA‐inflammation‐ICAS pathways. Future clinical researches with a larger scale and a higher power are still required to improve the precision of exploring miRNAs in patients with ICAS, so as to gain a better understanding of ICAS pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of ε2 has been associated with lower LDL-C level but with no in uence on HDL-C level [34]. Another study showed that the C allele of SNP rs2910164 of the miR-146a gene is a risk factor for atherosclerotic cerebral infarction (ACI) and that APOE ε4 may enhance ACI susceptibility by reducing miR-146a expression [36].…”
Section: Discussionmentioning
confidence: 99%